Mechanism of hot ductility loss in C–Mn steels based on nonequilibrium grain boundary segregation of impurities - Zheng, Zongwen; Yu, Hongyao; Liu, Zhenjun; Xu, Tingdong; Misra, R. Devesh K. (Journal of materials research, 2015)
The subject of hot ductility in C–Mn steels has been the focus of interest for a long time in materials science and engineering. However, the mechanism of loss in hot ductility continues to be unclear. In the present paper, the experimental hot ductility data in C–Mn steels involve: (i) a ductility trough appears at a certain temperature when the sample is held for a certain time at various temperatures after cooling quickly from a higher temperature; (ii) the ductility healing phenomenon which occurs with the duration of holding time; (iii) the ductility deteriorates with the increase of temperature difference between solution treatment temperature and test temperature during a tensile test; (iv) a minimum ductility appears when samples are cooled from a higher temperature to a lower one at a certain cooling rate; and (v) the formation of cavities at grain boundaries during tests. All of these are analyzed and calculated from the perspective of thermally induced nonequilibrium grain-boundary segregation (TNGS). Based on our detailed analyses, the loss in hot ductility of C–Mn steels is ascribed to TNGS of impurities.